HOW ARTIFICIAL INTELLIGENCE CAN BE EFFECTIVE FOR TEACHING ENGLISH TO HEARING IMPAIRED LEARNERS? - Deden Novan Setiawan Nugraha; Susiyanti Rusyan; Dianita Dianita (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2023)
Many applications and algorithms that were previously impossible to perform on a notebook, computer, or mobile phone may now be readily implemented thanks to growing sophisticated technology and increasingly powerful processing capabilities on computers. Artificial Intelligence (AI) is one technology that is gaining popularity for a variety of applications. To increase hearing impaired knowledge of English, an effective learning technique is required. One method is to apply artificial intelligence to a technology-based learning medium, such as Kahoot. The purpose of this study is to examine the efficiency of teachers in using English learning media based on Artificial Intelligence Kahoot at SDLB B Budi Nurani in Sukabumi City. This research employs a qualitative approach. Several teachers and students participated in this study. Data was collected through interviews, observation, and documentation and was processed descriptively and interpretively. The findings indicated that using Kahoot as a medium for learning English increased students' motivation and grasp of the English subject matter.